In Vivo Evaluation of the Position and Orientation of the Geometric Axis of the Tibiotalar Joint - Jian Yu; Shengxuan Cao; Chen Wang; Dahang Zhao; Shuo Wang; Chao Zhang; Jiazhang Huang; Xu Wang; Xin Ma (Applied Bionics and Biomechanics)
Background. Fitting the surface morphology of the talar trochlea is one of the common methods to define the geometric axis of the tibiotalar joint (GATJ). However, the in vivo motion of such axis during gait has not been fully investigated. Methods. The ankle kinematic data of fifteen volunteers were collected by a dual fluoroscopic imaging system with a model-image registration method. The GATJ was defined by sphere-fitting the medial or lateral part of the trochlear surface of the talus. The position and orientation of this axis during gait were measured. To verify this axis, the distances of the feature points of the talus to the GATJ during gait were also measured. Results. There was no statistically significant difference in the distances of feature points of the talus to the GATJ among the seven key poses of the gait cycle. And the position and orientation of the GATJ during gait also showed no statistically significant difference. Conclusion. The GATJ is the axis about which the talus rotated. And it is one fixed axis during gait. The current finding may help the design of the talar component for total ankle replacement based on the surface morphology of the talar trochlea.